First confirmation of Pseudogymnoascus destructans in British bats and hibernacula. (18th July 2015) - Barlow, A. M.; Worledge, L.; Miller, H.; Drees, K. P.; Wright, P.; Foster, J. T.; Sobek, C.; Borman, A. M.; Fraser, M.
Abstract : White‐nose syndrome (WNS) is a fatal fungal infection of bats in North America caused by Pseudogymnoascus destructans. P. destructans has been confirmed in Continental Europe but not associated with mass mortality. Its presence in Great Britain was unknown. Opportunistic sampling of bats in GB began during the winter of 2009. Any dead bats or samples from live bats with visible fungal growths were submitted to the Animal Health and Veterinary Laboratories Agency for culture. Active surveillance by targeted environmental sampling of hibernacula was carried out during the winter of 2012/2013. Six hibernacula were selected by their proximity to Continental Europe. Five samples, a combination of surface swabs or sediment samples, were collected. These were sent to the Center for Microbial Genetics and Genomics, Northern Arizona University, for P. destructans PCR. Forty‐eight incidents were investigated between March 2009 and July 2013. They consisted of 46 bat carcases and 31 other samples. A suspected P. destructans isolate was cultured from a live Daubenton's bat ( Myotis daubentonii ) sampled in February 2013. This isolate was confirmed by the Mycology Reference Laboratory, Bristol (Public Health England), as P. destructans . A variety of fungi were isolated from the rest but all were considered to be saprophytic or incidental. P. destructans was also confirmed by the Center for Microbial Genetics and Genomics in five of the six sites surveyed.